Congenital dyserythropoietic anemia type II and ineffective erythropoiesis: challenges in diagnosis and management - Akpan, Imo J.; Bogyo, Kelsie; Leeman-Neill, Rebecca J.; Wattacheril, Julia; Francis, Richard O. (Frontiers in Hematology, 2024)
Congenital dyserythropoietic anemia (CDA) is characterized by anemia—mild to severe, hemolysis, ineffective erythropoiesis, and in some cases, iron overload. There are three major types of CDA (I, II, and III), and the other types are rarer. The rarity of this disease, as well as signs and symptoms that overlap with other hematological diseases, can make the diagnosis difficult and delayed over several years. Evaluation includes basic laboratory testing, magnetic resonance imaging of organs for assessment of iron overload, bone marrow assessment, and genetic testing. Laboratory tests to evaluate for ineffective erythropoiesis include indirect bilirubin level, which can be normal or increased, reticulocyte production index < 2 signifying hyperproliferation of erythrocytes, and complete iron panel (serum iron, ferritin, and iron saturation), which may suggest iron overload. Genetic testing is crucial for CDA diagnosis and includes next-generation sequencing. A multidisciplinary team of providers including a hematologist, hepatologist, hematopathologist, and genetic counselor are important and sometimes necessary for the evaluation, diagnosis, and management of these patients. Management depends on the clinical phenotype, and some severe cases may require blood transfusion, iron chelation therapy, splenectomy, and in extreme cases, hematopoietic stem cell transplant may be necessary. This mini-review illustrates the challenges involved in the diagnosis and management of the most common CDA, which is type II. It will highlight clinical signs and symptoms in patients that should prompt providers to test for CDA. It will also increase awareness of this disease, discuss possible barriers to testing, and provide guidance on how to manage the disease.